Konsep Arsitektur Modern Pada Perancangan City Hotel Bintang 5 Di Kota Banda Aceh - Rafi Hidayat (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
Banda Aceh City is a city of Islamic Tourism Destinations in the World. This makes the city of Banda Aceh one of the tourist destinations in Indonesia for domestic and foreign tourists. So that the impact on increasing the number of tourists visiting the city of Banda Aceh in the last five years. The increasing number of tourists visiting the city of Banda Aceh is not comparable with the number of starred hotel accommodations that are able to serve tourists with good hotel facilities. Currently Banda Aceh City does not yet have a five-star hotel. Judging from the Room Occupancy Rate (TPK) of star hotels in 2016 to 2017, it increased by 2.38%, which was 46.08% to 48.46%. [1]. This makes enthusiasts who sleep in star hotels increasingly. From these problems, it is necessary to design a 5-star City Hotel and hotel facilities that are able to provide maximum service. The design of this City Hotel uses the theme of Modern Architecture. From the theme of Modern Architecture, there are several principles that will be used in the design so that the shape of the building matches the principles of the existing theme.AbstractBanda Aceh City is a city of Islamic Tourism Destinations in the World. This makes the city of Banda Aceh one of the tourist destinations in Indonesia for domestic and foreign tourists. So that the impact on increasing the number of tourists visiting the city of Banda Aceh in the last five years. The increasing number of tourists visiting the city of Banda Aceh is not comparable with the number of starred hotel accommodations that are able to serve tourists with good hotel facilities. Currently Banda Aceh City does not yet have a five-star hotel. Judging from the Room Occupancy Rate (TPK) of star hotels in 2016 to 2017, it increased by 2.38%, which was 46.08% to 48.46%. [1]. This makes enthusiasts who sleep in star hotels increasingly. From these problems, it is necessary to design a 5-star City Hotel and hotel facilities that are able to provide maximum service. The design of this City Hotel uses the theme of Modern Architecture. From the theme of Modern Architecture, there are several principles that will be used in the design so that the shape of the building matches the principles of the existing theme. Keywords: city hotel, modern architecture